Islamic Group Guidance to Improve The Religiosity and Readiness to Face Death (Jurnal Bimbingan Konseling, 2019)
The purposes of this study were to analyze the religiosity and readiness to face death before and after receiving Islamic group guidance, and analyze the effectiveness of Islamic group guidance to improve the religiosity and readiness to face death of the members of PWRI Jakarta. This study used experimental method with the design of one group pre-test – post-test by involving as many as 8 people as research subjects. For more, the results of Wilcoxon analysis showed that the level of religiosity of PWRI members got improvement in the post-test when compared to the results of their pre-test (z =-2.52; p < 0.01). Besides, the readiness to face death of PWRI members also increased in the post-test when compared to the results of their pre-test, (z = -2.52; p < 0.01). In conclusion, the results of this study assert that Islamic group guidance contributes the improvement of religiosity and readiness to face death.